Cryogenic Machining-Induced Surface Integrity: A Review and Comparison with Dry, MQL, and Flood-Cooled Machining - KAYNAK, YUSUF (TAYLOR & FRANCIS INC, 2014)
The process of cryogenic machining, due to increased demand for environmentally friendly manufacturing processes, has seen a growing interest in the machining community. This article presents an overview of cryogenic machining and its induced surface integrity characteristics such as surface roughness, topography, grain refinement and machining-induced layer, microhardness, phase transformation, residual stress and fatigue life in machining of various materials including difficult-to-machine materials, aerospace alloys, lightweight materials, etc. The effect of cryogenic machining on surface integrity characteristics is discussed, and compared with dry, Minimum Quantity Lubrication (MQL), and flood-cooled machining processes. In addition to being an environmentally friendly process, this study shows that cryogenic machining significantly contributes to improved functional performance of machined components through its superior and more desirable surface integrity characteristics.
Keywords: flood-cooled machining; functional performance; surface integrity; minimum quantity lubrication (MQL); cryogenic machining; NICKEL-BASED SUPERALLOY; TOOL-WEAR; LIQUID-NITROGEN; WHITE LAYERS; TITANIUM-ALLOY; AISI 304-STAINLESS-STEEL; CUTTING FORCES; PERFORMANCE; STEEL; IMPROVEMENT